Impact of financial indicators on stock price movement: evidence from listed manufacturing companies in sri lanka - Rubika, M.; Paviththira, P. (University of Jaffna, 2016)
Over time market players have developed much interest in factors that bring about movement or change in share price in the stock market either upward movement or downward movement several issues have been adduced for this over the years. This study explores analysis of the influence of financial indicators on stock price movement covering the period 2009-2014, sample drawn from the listed manufacturing industry. The sample consists 15 manufacturing companies listed on Colombo stock exchange (CSE). In order to examine the analysis of financial indicators on stock price movement, the current ratio (CR), dept equity ratio (D/E Ratio), assets turnover ratio, price earnings ratio (P/E Ratio) and Firm Size (FS) were used as independent variables, whereas market price per share (MPS) is used as the dependent variable. Data of the selected firms which are listed in the Colombo stock exchange (CSE) Sri Lanka were obtained from their websites. The statistical tests were used includes: descriptive statistics, correlation and regression analyses. Through the multiple correlation analysis with the help of user friendly statistical software it is found, there is significant and positive association between MPS and CR (P= 0.008, < 0.01). Which indicate that, as the CR increases it would tend to increase the MPS of the company, On the other hand, there is significant and positive correlation between MPS and FS (P=0.001, < 0.01). Which indicate that, as the FS increases it would tend to increase the MPS of the company.
Keywords: Colombo stock exchange; Financial indicators; Market price per share